Adoption of Resource Conservation Technologies and Its Impact on Wheat Cultivation in Haryana - Kumar, Anuj; Singh, Randhir; Singh, Satyavir; R, Sendhil; Chand, Ramesh; Pandey , JK (Indian Journal of Extension Education, 2017)
The study was conducted in Kaithal district of Haryana during 2014-15 in nine villages with 120 purposively selected  farmers who have adopted either of the three resource conservation technologies viz; zero tillage, rotary tillage and laser  land leveller or in combination. Majority (68.98 %) of the farmers belonged to middle age group (31-50 years) followed  by young (20.33 %) and old (18.69 %). Majority (85 %) of the farmers were literate and agriculture was their main  occupation. Farmers were categorised in four groups on land holding basis and 6.5 per cent, 15.46 per cent, 39.02 per cent  and 39.02 per cent, in marginal, small, medium and large categories, respectively. In the study area, majority of the  farmers preferred Agriculture Development Officers (ADOs) as main source of information. The study on adoption  pattern of resource conservation technologies revealed that 69.92 per cent of the farmers had adopted zero tillage, 51.22  per cent rotary tillage, 67.48 per cent laser land leveller, 22.76 per cent zero tillage+rotary tillage, 47.15 per cent zero  tillage+laser land leveller, 33.33 per cent rotary tillage+laser land leveller and 13.01 per cent zero tillage+ rotary tillage+  laser land leveller. Majority (84.88 %) of the farmers used zero tillage for timely sowing and 40.70 per cent used for both  i.e. timely and late sown conditions. Regarding the impact of zero tillage technology, majority of the farmers (77.91 %)  told that there was saving of time under zero tillage sowing as compared to conventional tillage. Majority of the farmers  (80.23 %) told that there was an increase in broader leaf weeds under zero tillage and reduction in narrow leaf weed  population (80.23 %) and 76.74 per cent of them recorded reduction in overall weed population. All the farmers agreed  that there was cost saving under zero tillage technology. Most of them (91.86 %) harvested more yield as compared to  conventional tillage. A large number of farmers (61.63 %) observed longer crop duration (4-7 days), increased soil  fertility (51.16 %), increased organic carbon in the soil (54.65 %) and increased moisture retention capacity of soil (50  %) and less lodging (87.21 %) as compared to conventional tillage. All the farmers agreed that there was time saving  under rotary tillage in wheat sowing. Majority of them (68.25 %) recorded decrease in cost of cultivation, more yield  (41.27 %), increased soil fertility (86.96 %), increase in organic carbon content of soil (57.14 %), increase in moisture  retention capacity of soil (52.33 %), avoidance of terminal heat (85.71 %) and increase in lodging (46.03 %). Due to  adoption of laser land leveller farmers (45.78 %) could save time in field preparation, 2-3 per cent increase in cultivable  area, less time required to irrigate the crop, 30-40 per cent water saving, more yield (96.39 %) and less lodging (95.18 %).
Keywords: Resource; conservation; technology; terminal heat; adoption; organic carbon; fertility; zero tillage; rotary tillage; laser land leveller